1972
DOI: 10.1002/star.19720241004
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Chemical Structure of Barley and Wheat Starch Granules

Abstract: Barley starch exists in two clearly defined populations of large (ca. 25 μ diameter) and small (ca. 5, μ diameter) granules, whilst in wheat there is a range of granule sizes with no similar bimodal distribution. The small granules of barley represent about 90% of the total starch granules by number, but account for only about 10% of the total starch in weight. Fractions containing only large or only small granules have been isolated from both barley and wheat. The small granules from barley have a higher amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

1973
1973
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 16 publications
0
25
1
Order By: Relevance
“…This layer was removed by careful scraping with a spatula and contained mostly small granules together with some large granules. 5 The lower starch cake contained mainly large granules with some small ones.…”
Section: Methodsmentioning
confidence: 97%
“…This layer was removed by careful scraping with a spatula and contained mostly small granules together with some large granules. 5 The lower starch cake contained mainly large granules with some small ones.…”
Section: Methodsmentioning
confidence: 97%
“…MacGregor and Morgan concluded that the difference was unlikely to be significant, because of the errors inherent in these determinations. Bathgate and Palmer (7) reported that the small starch granules isolated from mature barley kernels (cultivar Mans Otter) were far more resistant to gelatini zation than the large granules on the basis of polarising microscopy and the adsorption of Congo Red dye. Wider ranges of gelatinization and smaller heats of gelatinization of the small granules of waxy barley starches compared with those of large granules were shown by DSC (Table 5), as in the case of non-waxy barley starch (1).…”
Section: ) Pasting Characteristics Of Waxy Barley Starches By Dscmentioning
confidence: 99%
“…As to barley starches, older procedures employing light microscopy, liquid sedimentation balance (NOVOTNÝ 1970;BANKS et al 1973), and micro-sieving (BAGHATE & PALMER 1972;EVERS et al 1974) were used. Later, in 90's, so-called "Coulter Counter method" was very popular, in which starch granules were classified by size related to their effect on the electrical resistance of an electrically conductive liquid (MCDONALD & STARK 1988;SOUTH & MORRISON 1990).…”
Section: Determination Of the Contents Of A-and B-starches In Barley mentioning
confidence: 99%